2014
DOI: 10.3109/00016357.2014.898091
|View full text |Cite
|
Sign up to set email alerts
|

A cone-beam computed tomography study of root canal morphology of maxillary and mandibular premolars in a Turkish population

Abstract: CBCT scanning provides comprehensive information about the root canal morphology of maxillary and mandibular premolar teeth. These data may help clinicians in root canal treatment of premolar teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
94
7
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 20 publications
33
94
7
7
Order By: Relevance
“…Several studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) have reported that maxillary premolars have a highly variable internal canal configuration, which can vary according to race and geographic origin (8,9,12). The reported prevalence of maxillary first premolars with 1 root ranges from 22% to 66%, with 2 roots from 33% to 84%, and with 3 roots from 0% to 6% (7,8,11,12,16,17,20).…”
mentioning
confidence: 95%
“…Several studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) have reported that maxillary premolars have a highly variable internal canal configuration, which can vary according to race and geographic origin (8,9,12). The reported prevalence of maxillary first premolars with 1 root ranges from 22% to 66%, with 2 roots from 33% to 84%, and with 3 roots from 0% to 6% (7,8,11,12,16,17,20).…”
mentioning
confidence: 95%
“…The presence of three root canals in maxillary premolars of the Turkish population is a very rare occurrence as reported by several studies. [5][6][7] Ok et al [7] revealed that the incidence of three-canalled maxillary first premolars and second premolars in the Turkish population was 1.2% and 0.3% respectively. However, Calişkan et al [5] showed that it has been shown not to be found three-rooted first and second premolars in the Turkish population Mandibular premolars usually have one root and one canal.…”
Section: Discussionmentioning
confidence: 99%
“…However, two to four canals have also been reported. [11,12] Ok et al [7] revealed that the incidence of threecanalled mandibular first premolars and second premolars in the Turkish population was 0.06% and 0.2% respectively. On the other hand, Calişkan et al [5] showed that the incidence of three-rooted mandibular first and second premolars in the Turkish population was 5.66% and 0.00% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations